Pre-treatment of palm oil mill effluent (POME) : a comparison study using chitisan and alum - Abu Hassan, Mohd. Ariffin (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2007)
Chitosan is a natural organic polyelectrolyte of high molecular weight and charge density; obtained from deacetylation of chitin. This study explored the potential and effectiveness of applying chitosan as a primary coagulant and flocculent, in comparison with aluminium sulphate (alum) for pre-treatment of palm oil mill effluent (POME). A series of batch coagulation and flocculation processes with chitosan and alum under different conditions, i.e. dosage and pH were conducted, in order to determine their optimum conditions. The performance was assessed in terms of turbidity, total suspended solids (TSS) and chemical oxygen demand (COD) reductions. Chitosan showed better parameter reductions with much lower dosage consumption, compared to alum, even at the original pH of POME, i.e. 4.5. At pH 6, the optimum chitosan’s dosage of 400 mg/L was able to reduce turbidity, TSS and COD levels by 99.90%, 99.15% and 60.73% respectively. At this pH, the coagulation of POME by chitosan was brought by the combination of charge neutralization and polymer bridging mechanism. As for alum, the optimum dosage was 8 g/L at pH 7 which result in reductions of turbidity, TSS and COD by 99.45%, 98.60% and 49.24%, respectively. Combinations of chitosan and alum, showed very little increment in efficiency, compared to using chitosan alone. It can be suggested that polymer bridging mechanism by chitosan is more dominant than alum and the dosage of alum can also be reduced.